KONSEP KOMARUDDIN HIDAYAT TENTANG TERAPI KETAKUTAN TERHADAP KEMATIAN - Mega Herdina (Jurnal Studia Insania, 2013)
It is normal that human beings fear death, even though everybody knows that, one day, he or she will die. Death is scary because one does not know wat will happen after death. A person who feels happy in this life will also fear death because he/she will leave the happy life. Komaruddin Hidayat, in his popular book, Psikologi Kematian, tries to discuss this problem. He suggests that in order to face death calmly, one has to know what death is, and what will happen to him/her in the life after death. He also maintains that, abstention from worldly pleasures may help one to be ready to face death. Above all, for him, the most important thing to do is to find the meaning of life.